2015
DOI: 10.1007/s00192-015-2887-2
|View full text |Cite
|
Sign up to set email alerts
|

Prolapse or incontinence: what affects sexual function the most?

Abstract: Introduction and hypothesisPelvic organ prolapse (POP) and stress urinary incontinence (SUI) adversely affect sexual function in women. Comparative studies of the two subgroups are few and results are conflicting. The aim of this study was to compare the effect of POP and SUI on the sexual function of women undergoing surgery for these conditions.MethodsThe study population comprised women with POP or SUI in a tertiary referral hospital in the UK. Women who underwent SUI surgery had no symptoms of POP and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
(29 reference statements)
1
18
0
1
Order By: Relevance
“…II. Jha et al 5 reported that the absence of sexual activity among women with POP was greater than that among women with UI. Moroni et al 19 claimed that, among women with POP, the anatomical features of the prolapse did not appear to interfere with genital body image or with sexual function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…II. Jha et al 5 reported that the absence of sexual activity among women with POP was greater than that among women with UI. Moroni et al 19 claimed that, among women with POP, the anatomical features of the prolapse did not appear to interfere with genital body image or with sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…The demand for evaluation and treatment of these conditions has steadily increased in recent years, with increased life expectancy and efforts to promote quality of life (QoL). 4,5 Sexuality is a fundamental part of human life, and is an important parameter for health and QoL. 6 Thus, the current study sought to identify factors that affect sexual activity in women with PFD, and the impacts of QoL, according to sexual activity status.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found an association between pelvic floor disorders and overall poorer sexual function [7,8] with up to 60% of sexually active women attending urogynecology clinics reporting sexual dysfunction [5]. However, there are conflicting results regarding the different effects of urinary incontinence and pelvic organ prolapse over overall sexual function [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…As to the different effects of different pelvic floor disorders over components of sexual dysfunction, research has suggested that prolapse is more likely than urinary incontinence to result in sexual inactivity [9,10], especially when bulging of genital organs is presented [8]. Other studies report that urinary incontinence is related to infrequent orgasm [11], low libido, vaginal dryness and dyspareunia [12].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical symptoms of POP include incontinence, constipation, vaginal pressure and sexual dysfunction . POP is a serious health problem, which is associated with quality of life, sexual function and psychological state . UI is divided into several types, and it affects up to approximately 41% of women worldwide .…”
Section: Introductionmentioning
confidence: 99%